Wittgenstein and philosophy of religion - Addis, Mark; Arrington, Robert L. (Routledge, 2001)
Book Cover; Title; Contents; Contributors; Editors' introduction; Acknowledgements; Abbreviations; The gospel according to Wittgenstein; Wittgenstein and magic; Wittgenstein, religious belief, and On Certainty; Creation, causality, and freedom of the will; Faith: themes from Wittgenstein, Kierkegaard and Nietzsche; D.Z. Phillips' fideism in Wittgenstein's mirror; Wittgensteinian religion and 'reformed' epistemology; Wittgenstein and the interpretation of religious discourse; Wittgenstein and Wittgensteinians on religion; 'Theology as grammar': Wittgenstein and some critics; Index.